2017
DOI: 10.1371/journal.pone.0173465
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis confirms the long-distance transport of Juniperus ashei pollen

Abstract: Although considered rare, airborne pollen can be deposited far from its place of origin under a confluence of favorable conditions. Temporally anomalous records of Cupressacean pollen collected from January air samples in London, Ontario, Canada have been cited as a new case of long-distance transport. Data on pollination season implicated Juniperus ashei (mountain cedar), with populations in central Texas and south central Oklahoma, as the nearest source of the Cupressacean pollen in the Canadian air samples.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…Although cypress trees are typical of Mediterranean regions, Cupressaceae pollen dispersal also affects non‐Mediterranean environments, including Central Europe, North America, Mexico and Japan . GRP‐related allergy to Rosaceae and Citrus fruits was reported in conjunction with Japanese cedar pollinosis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although cypress trees are typical of Mediterranean regions, Cupressaceae pollen dispersal also affects non‐Mediterranean environments, including Central Europe, North America, Mexico and Japan . GRP‐related allergy to Rosaceae and Citrus fruits was reported in conjunction with Japanese cedar pollinosis .…”
Section: Discussionmentioning
confidence: 99%
“…GRP‐related allergy to Rosaceae and Citrus fruits was reported in conjunction with Japanese cedar pollinosis . In south‐central United States, mountain cedar ( Juniperus ashei ) pollen is a major cause of allergic rhinoconjunctivitis . Pollinosis to Cupressaceae has been steadily increasing during the past decades, possibly as a result of extended species distribution due to climate change and ability of Cupressaceae pollen to travel over hundreds of kilometres .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,30,31 Cedar/juniper in particular has been found to travel long distances. 32 Wind direction was not included in this study, because a prior study of Denver pollen counts found that wind direction did not affect Denver pollen counts. 33 Other factors can affect the relationships we observed between meteorology and pollen counts, both now and in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Pollen is a type of bio-aerosol; Pinus pollen as well as other types of pollen travel long distances. This pollen is regarded as exotic, and many studies have investigated its source area and long-distance transportation by trajectory analyses [33][34][35][36][37]. For aerosols reaching ice sheets and mountain glaciers, dust has been used as a tracer for emission sources as well as large-scale atmospheric circulation [38][39][40].…”
Section: Potential Use Of Pollen Grains As a Tracer For Emission Sourcesmentioning
confidence: 99%